Maternal near-miss at Hospital Nacional Docente Madre-Niño San Bartolome, Lima, 2007-2009 - Armas, Iván Reyes (2013)
Objectives: To determine near-miss maternal morbidity (MME) at a National Teaching Hospital. Design: Observational, retrospective, transversal type study. Setting: Hospital Nacional Docente Madre-Niño San Bartolome, Lima, Peru. Participants: Pregnant and puerperal women. Interventions: Clinical charts of 206 patients attended between January 2007 and December 2009 and with consideration of extreme maternal morbidity related to specific disease, organic or management failure were revised. Socio-demographic and obstetric variables were analyzed following the protocol established in FLASOG´s methodology for surveillance, as well as identification of the basic cause of morbidityand delays established in the ‘route towards life’ methodology. Main outcome measures: Incidence and characteristics of patients. Results: Extreme maternal morbidity (EMM) affected 0.94% of patients at San Bartolome Hospital, with a mortality index of 0.032, maternal morbidity (MM) rate of 9.4 and EMM/MM of 30.4. It was related to maternal age above 35 years, low educational level, multiparity, failure of prenatal control, short or prolonged intergenesic period, preterm gestation, caesarean section, high perinatal mortality rate. Gestational hypertensive disease was the most important cause of EMM (42.2%), followed by puerperal hemorrhage (17.5%). Coagulation disorder occurred in 33.5%, transfusions were necessary in 27.2% and alteration of the renal function affected to 26.7% of cases. Delays related with service quality (type IV) were associated in 58.3% of cases of EMM. Conclusions: Extreme maternal morbidity affected an important number of cases at San Bartolome National Hospital, and the most frequent cause was gestational hipertensive disease.Key words: Extreme maternal morbidity.